Neuroprotective Effects of Ethanol Extract Polyscias guilfoylei (EEPG) Against Glutamate Induced Neurotoxicity in HT22 Cells - Sang, Nguyen Qui Ngoc; Yoo, Ki-Yeon; Pham Thi Thu Trang; Selvaraj, Baskar; Huong Thuy Vu; Tam Thi Le; Heesu Lee; Quang Luc Tran; Phuong Thien Thuong; Ae Nim Pae; Sang Hoon Jung; Lee, Jae Wook (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Oxidative stress induced by glutamate is a significant contributor to neuronal cell damage and can lead to neurodegenerative diseases such as Alzheimer’s, Huntington’s, and ischemic brain injury. At the cellular level, oxidative stress increases Ca2+ ion influx and reactive oxygen species (ROS), which activate the MAPK signaling pathway. Additionally, the generation of ROS causes mitochondrial dysfunction, triggering apoptosis by promoting the translocation of AIF to the nucleus from the mitochondria. The neuroprotective potential of Polyscias guilfoylei has not yet been reported. Therefore, in this study, the ethanol extract of Polyscias guilfoylei (EEPG) was examined for its protective effect against oxidative cell damage caused by glutamate in neuronal cells. EEPG treatment increased the viability of HT22 cells exposed to high concentrations of glutamate. Cellular Ca2+ ion influx and ROS generation decreased with EEPG treatment in glutamate-treated HT22 cells. EEPG treatment inhibited MAPK activation and AIF nuclear translocation. In an in vivo study, EEPG attenuated brain cell death in an ischemic brain injury rat model. This study demonstrates the potential therapeutic effects of Polyscias guilfoylei in the treatment of ischemic brain injury.